The Role of the Sharia Supervisory Board in Mediating Disclosure of Islamic Social Reporting and the Quality of Financial Reports on the Reputation of Sharia Banking in Indonesia - Wan Haerul Bariah; Indria Puspitasari Lenap (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the role of DPS in mediating ISR disclosure and the quality of financial reports on the reputation of sharia banking in Indonesia. The type of research used is associative with a quantitative approach. This research used a purposive sampling technique, where from the criteria results, 45 observations of Sharia Commercial Banks in Indonesia were obtained for 5 years. The data analysis technique used is panel data regression with the Eviews 12 application. The research results show that ISR disclosure and the quality of financial reports have no effect on the reputation of sharia banking. Meanwhile, the number of DPS influences the reputation of sharia banking. This research also found that the role of DPS was unable to mediate the relationship between ISR disclosure and the quality of financial reports on the reputation of sharia banking.